Rekonstruksi Figur Perempuan dalam #metoo di Instagram - Fernando, Henky; Larasati, Yuniar Galuh (Jurnal Komunikasi, 2024)
The dissemination of female figures on Instagram not only represents a reality, but is also a reconstruction over reality. The study explains the forms and factors that influenced the emergence of female figure reconstruction in #metoo on Instagram. The study uses the netnography method. The data was taken from a woman's post in #metoo on Instagram. The findings in this study show that the reconstruction of the female figure in #metoo on Instagram emphasizes two forms, namely the reconstitution of the attitude of women from passive to active, and the reconstruction of female identity from inferior to superior. Such reconstruction is predominantly influenced by structural and cultural factors that are not uncommonly discriminatory and intimidating against women. The study also recommends the importance of a study that explains the conception of subjects against female figure reconstruction in #metoo by interviewing a group of women who are actively using Instagram to gain a more comprehensive and empirical understanding.